PERANCANGAN SISTEM INFORMASI AKUNTANSI TERKOMPUTERISASI ATAS SIKLUS PENGGAJIAN PADA PT. DUTA AUDIO INTI DI SURABAYA - KRISTANTI, AMEYLIA (Universitas Katolik Widya Mandala Surabaya, 2012)
PT. Duta Audio Inti is a company specialized in the supply of rental services sound system and generator. As long as these companies use manual accounting information system for payroll cycle, in which the system is not adequate because the system is not able to information needs of the company. Information generated from manual payroll system is often inaccurate and require a lot of time and effort to obtain the desired information. Therefore, this study aims to create a computerized accounting information system design for the payroll cycle at PT. Duta Audio Inti in Surabaya so as to meet the needs of the company payroll information accurate and timely and can minimize the errors that occur within the company. This study is a applied research with case study. Type of data used in this study is qualitative data and data sources in this study come from internal sources, form the primary data obtained directly from the company as its source. The method used is a preliminary study and field studies include observation, interview and documentation. Techniques of analysis in this study follow the steps in the System Development Life Cycle (SDLC) that is systems analysis, conceptual design and physical design. The results of this study are the conceptual design of the Data Flow Diagram (DFD) and Entity Relationship Diagram (ERD), physical design includes output design, database design, input design, control matrix design, decision tables design, and control applications design. With this information system had planned, expected to overcome the problems that occur in the company's payroll cycle.